Explore BrainMass

Explore BrainMass

    Derivatives of Functions Simplified

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Find the derivative of the function and simplify.

    y= (3x^2 + 7) (x^2 - 2x)

    s= (4 - 1/t^2)(t^2 -3t)

    f(x)= x^2 + x - 1/ x^2 -1

    f(x)=^3 sqrt(x^2 -1)

    g(x)= sqrt (x^6 - 12x^3 + 9)

    © BrainMass Inc. brainmass.com October 5, 2022, 2:21 pm ad1c9bdddf

    Solution Summary

    The derivatives of functions are simplified.